Health behaviors and mental health among adolescents: A comparison based on BMI using the 2021 Korea Youth Risk Behavior Survey - Hye-Ryeon Park; Na-Geong Kim (Belitung Raya Foundation, Indonesia, 2023)
Background: Obesity and underweight can have adverse effects on adolescents. However, previous obesity management program conducted in Korea for adolescents with obesity showed low effectiveness, and there are few studies on underweight Korean adolescents. Objective: This study aims to analyze differences in the health behaviors and mental health of adolescents based on their body mass index (BMI). Methods: Data from the 2021 Korea Youth Risk Behavior Survey were examined. The health behaviors and mental health of 53,445 adolescents were analyzed according to BMI using SAS version 9.4 with the Rao-Scott χ2 test and logistic regression analysis. Results: Regarding the difference in health behaviors according to BMI, a higher proportion of participants who are drinking alcohol and are exposed to secondhand smoke were in the underweight group than in the obesity group. The rate of obesity among those engaged in physical activity was higher than that among those involved in non-physical activity. In addition, the obesity group used smartphones more than the underweight group, while the quality of sleep was better among the underweight group than the obesity group. Conclusion: While the health behaviors and mental health of adolescents according to BMI are similar to those of previous studies, there are also distinct aspects. Consequently, further exploration of health behaviors and mental health based on BMI is crucial for developing and implementing targeted nursing intervention programs for adolescents with different weights.